1977
DOI: 10.1111/j.1365-2672.1977.tb00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Sensitivity of the Limulus Assay for the Detection of Gram Negative Bacteria

Abstract: In the Limulus pyrogen assay a linear relationship has been demonstrated between optical density and viable cell number of the strains of Gram negative bacteria studied. When the bacteria are suspended in a solution of 0.9% saline and 10‐5 M‐ethylenediamine‐tetra‐acetic acid (EDTA) the sensitivity of the assay is markedly improved and the variation between different species or strains is greatly reduced. The Limulus assay is able to detect fewer than 103 of the least reactive Gram negative bacteria studied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results presented here showed no enhancing effect of EDTA treatment. However, the end point detection was probably less sensitive than that used by Coates (1977) and only treatments causing a change in sensitivity of at least a factor of ten would be apparent. An increase of this nature was apparent after sonication which improved the sensitivity of the assay to cells of P. putida and P. fragi by an order of magnitude.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results presented here showed no enhancing effect of EDTA treatment. However, the end point detection was probably less sensitive than that used by Coates (1977) and only treatments causing a change in sensitivity of at least a factor of ten would be apparent. An increase of this nature was apparent after sonication which improved the sensitivity of the assay to cells of P. putida and P. fragi by an order of magnitude.…”
Section: Discussionmentioning
confidence: 90%
“…However, Jay (1977) did note that the values he obtained for the minimum number of cells required to give a positive titre were approximately ten-fold higher than those reported by other workers. Coates (1977) using a spectrophotometric method found that treatment with EDTA/Tris/HCl increased the sensitivity of the Limu1u.s assay to LPS. The results presented here showed no enhancing effect of EDTA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Maeda & Taga, 1979;Flowers, 1979;Coates, 1977;Janda & Work, 1971). This extremely sensitive test is used mainly to detect bacteria in medical fluids.…”
Section: Introductionmentioning
confidence: 99%
“…It should further be realized that the LPS content depends on the growth phase (111) and that correction factors must be introduced when heat-treated foods (UHT milk, dried milk) are being examined. Because the evaluation of gel strength is subjective, a modification was developed in which the coagulation was determined turbidimetrically (112) or colorimetrically with the help of a chromogenic substrate (113)(114)(115), which after activation of the proteolytic system liberates a colored product quantifiable by measuring at 405 nm. Although at present not commercially available, the LAL test with chromogenic substrate is suitable for automation (116,117).…”
Section: Principlementioning
confidence: 99%